The black hole at the center of our galaxy - Melia, Fulvio (Princeton University Press, 2018)
Could Einstein have possibly anticipated directly testing the most captivating prediction of general relativity, that there exist isolated pockets of spacetime shielded completely from our own? Now, almost a century after that theory emerged, one of the world's leading astrophysicists presents a wealth of recent evidence that just such an entity, with a mass of about three million suns, is indeed lurking at the center of our galaxy, the Milky Way--in the form of a supermassive ''black hole''! With this superbly illustrated, elegantly written, nontechnical account of the most enigmatic astronomical object yet observed, Fulvio Melia captures all the excitement of the growing realization that we are on the verge of actually seeing this exotic object within the next few years. Melia traces our intellectual pilgrimage to the ''brooding behemoth'' at the heart of the Milky Way. He describes the dizzying technological advances that have recently brought us to the point of seeing through all the cosmic dust to a dark spot in a clouded cluster of stars in the constellation Sagittarius. Carefully assembling the compelling circumstantial evidence for its black hole status, he shows that it is primed to reveal itself as a glorious panorama of activity within this decade--through revolutionary images of its ''event horizon'' against the bright backdrop of nearby, radiating gas. Uniquely, this book brings together a specific and fascinating astronomical subject--black holes--with a top researcher to provide both amateur and armchair astronomers, but also professional scientists seeking a concise overview of the topic, a real sense of the palpable thrill in the scientific community when an important discovery is imminent.